Lipušev novi preboj regionalizma - Paternu, Boris (Jezik in slovstvo, 2003)
With his contemporary narrative Boštjanov let (2003), Florjan Lipuš (1937) created an example of prose which is Carinthian, regional in its thematic and linguistic or even dialectal origins; with its content and stylistic aptitude, however, it is open to the world of modern literature culture. The main focus of the book in on child's (Boštjan's) war and linguistic trauma, and a trauma arising from the provincial and conservative envirinment from which he painfully works his way through towards his own otherness and freedom. The linguistic stategy of the narration incorporates a strong inner tension between linguistic archaism, which Lipuš raises to the level of contemporary literary language, and modern intellectualisation and stylisation that he stimulataneously lowers into what is today an aincent folk, dialectal discourse. It is hardly a coincidence that at the time of an enveloping globalisation this linguistic fortification of the Slovene languagehas come forth in the area that is linguistically most endangered, a fact which had seriously affected Lipuš in his young days.
Keywords: Lipuš, Florjan, 1937-; Slovene literature; slovenska književnost; ocene in poročila; literarne študije; Lipuš, Florjan: Bioštjanov let